1987
DOI: 10.1111/j.1365-2761.1987.tb01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, microbiological and epidemiological findings in recent outbreaks of goldfish ulcer disease due to atypical Aeromonas salmonicida in south‐eastern Australia

Abstract: The spread of goldfish ulcer disease (GUD) from Victoria to New South Wales, Austraha, and the first isolation oi Aeromonas salmonicida from wild goldfish are reported. Cultural, biochemical and protein SDS-PAGE characteristics of these recent isolates are compared with those of existing Australian isolates, with strains recovered from goldfish in Italy and the USA (atypical strains) and with strain ATCC 14174 (typical strain). The Australian isolates were identical and closely resembled the exotic atypical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Our results regarding the usefulness of selected biochemical tests for the classification of AS are in agreement with earlier reports (Paterson et al 1980, Popoff 1984, Bohm et al 1986, Whittington et al 1987, Wichardt et al 1989, Olivier et al 1990, Toranzo et al 1991), but we also found acid production from L-arabinose and hydrolysis of Tween 80 to be useful in differentiating between typical and atypical strains. According to Popoff (1984), all AS strains were positive in the Tween 80 degradation test, while we found all the typical isolates to be positive and the atypical ones negative, as reported by Austin et al (1989).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results regarding the usefulness of selected biochemical tests for the classification of AS are in agreement with earlier reports (Paterson et al 1980, Popoff 1984, Bohm et al 1986, Whittington et al 1987, Wichardt et al 1989, Olivier et al 1990, Toranzo et al 1991), but we also found acid production from L-arabinose and hydrolysis of Tween 80 to be useful in differentiating between typical and atypical strains. According to Popoff (1984), all AS strains were positive in the Tween 80 degradation test, while we found all the typical isolates to be positive and the atypical ones negative, as reported by Austin et al (1989).…”
Section: Discussionsupporting
confidence: 93%
“…It is very important, therefore, to be able to differentiate between typical and atypical strains of AS. There are numerous articles discussing the taxonomy of AS (McCarthy 1977, McCarthy & Roberts 1980, Paterson et al 1980, Popoff 1984, Bohm et al 1986, Whittington et al 1987, Wichardt et al 1989, Olivier & Moore 1990, Toranzo et al 1991. In this study the biochemical profiles of typical and atypical AS strains isolated in Finland were compared and their antimicrobial sensitivities determined.…”
Section: Introductionmentioning
confidence: 98%
“…Atypical A . salmonlcida have been reported to have caused ulcerative lesions or other clinical signs in carp Cyprinus carpio (McCarthy 1977), minnow Phoxinus phoxinus (Hgstein et al 1978), Atlantic salmon Salmo salar (Paterson et al 1980), goldfish Carassius auratus (Elliott & Shotts 1980, Whittington et al 1987, Atlantic cod Gadus morhua (Cornick et al 1984), eel Anyuilla anguilla (Kitao et al 1985), sand-eels Ammodytes Jancea and Hyperoplus lanceolatus (Dalsgaard & Paulsen 1986), pike Esox lucjus (Wiklund 1990), and flounder Platichthys flesus (Wiklund & Bylund 1991).…”
mentioning
confidence: 99%
“…Humphrey & Ashburner (1993) (Trust et al 1980) and by 1985 had caused GUD on 2 fish farms in New South Wales and become enzootic in wild goldfish populations (Whittington et al 1987). In 1992, atypical A. salmonicida was isolated from cutaneous ulcers on silver perch Bidyanus bidyanus (Mitchell) with ulcerative dermatitis (R. Callinan, S. Rowland & R. Whittington unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…data). These fish were from a fish farm on which goldfish with GUD were detected in 1985 (Whittington et al 1987 1994). Goldfish with GUD were found in this lake in 1985, but roach examined at that time were unaffected (Whittington et al 1987).…”
Section: Introductionmentioning
confidence: 99%